2017
DOI: 10.5176/2345-7872_3.2_43
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Stigma on the Recognition of Suicide Risk in Others between Australia and Brazil

Abstract: Few studies have considered how suicide is perceived and impacted by stigma across cultures. A sample of 478 participants from Australia and Brazil was used to investigate cross-cultural perceptions of suicide and the impact of stigma on the recognition of suicide risk in others. The Interpersonal-Psychological Theory of Suicide framed a mixed method within and between groups design. English and Portuguese versions of an online survey were developed to assess perception of thwarted belongingness, perceived bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The subscales of the SOSS are obtained by calculating the mean response to all the items included in each subscale. All subscales have shown good internal consistency in previous studies with Cronbach alpha >.75 (Calear et al., ; Chan et al., ; Han, Batterham, Calear, Wu, Shou, et al., ; Peel et al., ). The Cronbach alpha of the stigma subscale was .86 in this study, while the normalization/glorification subscale was .79 and the isolation subscale .84.…”
Section: Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…The subscales of the SOSS are obtained by calculating the mean response to all the items included in each subscale. All subscales have shown good internal consistency in previous studies with Cronbach alpha >.75 (Calear et al., ; Chan et al., ; Han, Batterham, Calear, Wu, Shou, et al., ; Peel et al., ). The Cronbach alpha of the stigma subscale was .86 in this study, while the normalization/glorification subscale was .79 and the isolation subscale .84.…”
Section: Methodsmentioning
confidence: 70%
“…Conspicuously, more severe suicide ideation was associated with higher glorification of suicide, suggesting that further research might investigate whether glorification of suicide is an indicator for increasing risk in the clinical setting. In addition, the study demonstrated that the SOSS (short form) is likely to be valid for measuring the construct of suicide stigma within clinical populations, demonstrating a consistent factor structure and internal consistency similar to community samples (Batterham et al., ; Calear et al., ; Peel et al., ). These findings indicate that brief self‐report scales can feasibly be used to assess levels of suicide stigma and suicide literacy in clinical settings, where individuals are typically more vulnerable to suicide than in the general population.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, stigma and lack of knowledge on suicide may limit the development and implementation of effective suicide prevention strategies and healthcare interventions at the individual and community levels (Niederkrotenthaler et al, 2014 ). The evidence shows that increasing mental health literacy and lowering stigma towards suicidal persons are correlated with more positive attitudes towards seeking professional psychological help for mental health problems (Peel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this, research has yet to address the relationship between these factors and suicide stigma. This is particularly troublesome as suicide stigma can worsen the ability to recognize SIA in others, which is a vital skill for suicide prevention efforts in clinical interactions [ 24 ]. Thus, the purpose of this study was to examine the correlates of stigmatizing attitudes towards suicide in a sample of medical students in Puerto Rico.…”
Section: Introductionmentioning
confidence: 99%